IDENTIFIKASI KERAGAMAN GENETIK KERBAU LOKAL POPULASI JAWA TIMUR DAN NUSA TENGGARA BARAT BERBASIS MIKROSATELIT SEBAGAI MODEL PENGEMBANGAN KONSERVASI KERBAU SECARA EX SITU - Mohamad Amin; Umie Lestari (Universitas Sebelas Maret, 2014)
In Indonesia, local buffalo (Bubalus bubalis) is one type of germplasm that a major contribution in the national meat supply of animal protein. However, this germplasm will be reduced of its number. If this condition continues we will loss the germplasm . One effort to this is conservatuin based on a molecular marker mikrosatellite . Selected marker locus are HEL09 , INRA23 and ISLTS05 . Sampling area of it research in East Java and West Nusa Tenggara . The results showed that in both are and all loci is polymorphic, allele frequencies ranging from 0.125 to 0.875 and heterozygosity values in the range 35-65 % . These results illustrate that the two populations have genetic diversity that is still quite varied genotype . Key Words: alele frequency, heterozigosity, local buffalo, microsatellite